THE EFFECT OF RECIPROCAL TEACHING STRATEGY TOWARD STUDENTS’ MOTIVATION AND THEIR READING ABILITY AT SENIOR HIGH SCHOOL IN RAMBAH HILIR DISTRICT ROKAN HULU REGENCY - Syaiful; Zulpahmi Ahmad (JEE (Journal of English Education), 2017)
Based on the result of the preliminary study, it was found that the students at SMAN 1 Rambah Hilir and SMAN 3 Rambah Hilir werelow score and not interested reading class. The students tendedto be passive inlearning process. Their reading comprehension mastery was low and they needed a long time to understand a reading text, even short text. The purpose of this study was to find out the effect of reciprocal teaching strategy toward students‟ motivation and their reading ability at senior high school in Rambah Hilir District Rokan Hulu regency. The design of this research was a quasi-experimental research with pre-test and post-test procedure. The data were collected through test and questionnaire. The total population was 61 students‟ of SMA Negeri 1 Rambah Hilir and 41 students‟ of SMA Negeri 3 Rambah Hilir. This research applied a random sampling technique to get samples. Then, the data were analyzed by using t-test method to find out whether there is significant difference between the experimental group taught by using Reciprocal teaching strategy as a treatment, and the control group taught conventionally. The research result, the writer found that significant probabilities was higher than 0.05 (> 0.05) in both paired sample t-test and independent sample t-test, it meantthat there is significant different on students reading comprehension in pre-test both classes and in post-test of both classes, and there is significant different on students‟ motivation before and after treatment of experimental class. Besides, the value of eta square of students‟ was 0.97 at SMAN 1 Rambah Hilir and 0.96 at SMAN 3 Rambah Hilir. It showed it gave significant effect toward students‟ motivation and their reading ability